500 ICT Tips for Primary Teachers - Higgins, Steve (500 Tips, 1999)
Information and Communications Technology (ICT) has been the focus of much debate and development within education, especially in the primary sector. This text offers tried and tested ideas for using IT effectively across the whole primary curriculum.